2016
DOI: 10.1021/acsami.6b06883
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Diagnosis and Imaging-Guided Photothermal Therapy Using a Dual-Modality Nanoparticle

Abstract: To improve patient outcome and decrease overall health-care costs, highly sensitive and precise detection of a tumor is required for its accurate diagnosis and efficient therapy; however, this remains a challenge when using conventional single mode imaging. Here, we successfully designed a near-infrared (NIR)-response photothermal therapy (PTT) platform (Au@MSNs-ICG) for the location, diagnosis, and NIR/computer tomography (CT) bimodal imaging-guided PTT of tumor tissues, using gold (Au) nanospheres coated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…Xenografted nude mice treated with modified gold nanospheres after NIR laser exposure displayed a significant reduction in the tumor volume and facilitated distinct visualization of tumor tissue in vivo. The ICG loaded mesoporous silica core of the nanoparticles not only allowed potential tumor imaging ability, but also increased the heating efficiency of the gold metal, thus helping to facilitate NIR based image-guided PTT [55]. Kang et al conjugated NIR fluorophore cyptate to hollow gold nanospheres (HGNs) by a urokinase-type plasminogen activator (uPA a breast cancer enzyme) enzyme- substrate motif.…”
Section: Imaging and Photo-thermal Therapy Using Gold Nanoparticlesmentioning
confidence: 99%
“…Xenografted nude mice treated with modified gold nanospheres after NIR laser exposure displayed a significant reduction in the tumor volume and facilitated distinct visualization of tumor tissue in vivo. The ICG loaded mesoporous silica core of the nanoparticles not only allowed potential tumor imaging ability, but also increased the heating efficiency of the gold metal, thus helping to facilitate NIR based image-guided PTT [55]. Kang et al conjugated NIR fluorophore cyptate to hollow gold nanospheres (HGNs) by a urokinase-type plasminogen activator (uPA a breast cancer enzyme) enzyme- substrate motif.…”
Section: Imaging and Photo-thermal Therapy Using Gold Nanoparticlesmentioning
confidence: 99%
“…An updated overview on the development of new photosensitizers for anticancer photodynamic therapy was reported by Zhang et al, [30]. More clinical studies of the efficacy of PDT and PTT using various nanoparticles have been reported [31][32][33][34][35][36][37][38][39].…”
Section: Discussion Of Combined Ptt and Pdtmentioning
confidence: 99%
“…e) i) Preoperative PET-CT image, ii) intraoperative, and iii) postoperative images for LN mapping of a mouse with an orthotopic 4T1 breast tumor. [229] Tian's group successfully developed a CT/NIR imaging nanoplatform (Au@MSNs-ICG) by loading ICG-coated gold nanospheres into mesoporous silica NPs (MSNs), [231] on the basis of previous studies on ICG-loaded Au@SiO 2 . iv) SERRS imaging and v) the overlay of (ii) and (iv) of a tumor-bearing mouse with liver cancer.…”
Section: Pet/spect/ct-based Multimodal Imagingmentioning
confidence: 99%